2017
DOI: 10.12973/ejmste/79797
|View full text |Cite
|
Sign up to set email alerts
|

Extracurricular Activities at Modern Russian University: Student and Faculty Views

Abstract: This article deals with the problem of arranging extracurricular activities for students at a modern Russian university. Research interest in this issue stems from the fact that extracurricular activities are of great concern in the development of modern students' professionally important qualities and their professional competence. There is a critical need to change the approaches to the organization of extracurricular activities at a university in the light of modern tendencies of higher education developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…However, there is increasing interest in the potential for ECA to promote reflection. ECA are defined as voluntary activities that take place outside the class schedule [37], which complement curricular training [38] and contribute to the students' personal [39], professional [40], and social [41] development. These activities are classified into sporting, cultural, solidarity, spiritual and artistic activities, and student clubs [41][42][43].…”
Section: Eca (Extracurricular Activities) To Promote Reflective Learningmentioning
confidence: 99%
“…However, there is increasing interest in the potential for ECA to promote reflection. ECA are defined as voluntary activities that take place outside the class schedule [37], which complement curricular training [38] and contribute to the students' personal [39], professional [40], and social [41] development. These activities are classified into sporting, cultural, solidarity, spiritual and artistic activities, and student clubs [41][42][43].…”
Section: Eca (Extracurricular Activities) To Promote Reflective Learningmentioning
confidence: 99%
“…If U. S. and European universities offer various types of extracurricular activities, such as sport, music, art, academic clubs, in Russian universities an extracurricular life is not highly developed. Despite the fact that it is positively perceived by Russian students, a few of them are ready to take the initiative to organize a community with a specific mission [Ivanova, Logvinova, 2017]. Moreover, as some studies revealed, many students are not aware of student life activities in their institution as such activities are rarely supported and promoted by institutions [Belikova, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Participation in ECAs allows students to develop skills and attitudes that help them to understand other sociocultural realities, identify social problems, and participate in peaceful conflict resolutions [35]. Hence, it is argued that they promote lifelong learning, active citizenship and a sense of social justice, which enables students to assume more meaningful roles in society and face daily tasks with a more positive state of mind [4,36].…”
Section: Role Of Social Interactions In Developing An Ecamentioning
confidence: 99%
“…Currently, one of the biggest challenges in higher education is to foster personal attitudes among students that will enable them to move toward more equitable, just, and sustainable societies. In this 2 of 17 context, a growing body of literature has studied how ECAs contribute to this goal [3][4][5]. Furthermore, research in this field has indicated the impact of ECA in terms of achieving higher levels of academic performance [6], having more successful development during university life [7], improving later employment adaptation [8], and obtaining more significant social and psychological resources that aid the students' mental well-being [9].…”
Section: Introductionmentioning
confidence: 99%